Assessing the Effects of Leadership and Work Discipline on Employee Outcomes at Sukses Mulya Magelang Enterprise - Sari, Putri Kumala; Wijoyo, Tuwuh Adhistyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper seeks to examine the effects of leadership styles and work discipline on employee outcomes at Sukses Mulya Magelang Enterprise using qualitative research methodologies. The research investigates the impact of transformational and transactional leadership styles on employee motivation and performance via the use of semi-structured interviews and focus groups with workers and managers. The key results emphasize the crucial role of leadership in creating a supportive work environment and improving employee engagement. In addition, the research explores the significance of work discipline in upholding corporate norms and fostering responsibility among workers. Effective leadership and strong work discipline are essential for attaining corporate objectives and maintaining a competitive edge. The acquired insights assist to improving management practices and cultivating a constructive organizational culture at Sukses Mulya Magelang Enterprise